Experience with perceptual and motor skills in rhythmic gymnastics - Kioumourtzoglou, E.; Derri, V.; Mertzanidou, O.; Tzetzis, G. (Perceptual and Motor Skills, 1997)
Based on the notion of measuring motor performance, an experiment with three groups of 20 elite rhythmic gymnasts (N = 60), 9 to 10 yr., 11 to 12 yr., and 13 to 15 years of age (national level), with children of the same size and age was conducted, to identify the important abilities for the achievement of excellence in this sport. Motor abilities (whole-body coordination, dynamic balance, static balance, sense of kinesthesis, whole-body movement time, and eye-hand coordination) as well as perceptual abilities (whole-body reaction time, anticipation of coincidence, and depth perception) were compared. Analysis showed that scores on measures of whole-body coordination, dynamic balance, and static balance were higher for elite groups of athletes than for corresponding control groups. Moreover, elite athletes in the oldest group scored higher than those in the youngest group on anticipation of coincidence, on eye-hand coordination, and on static balance. These findings indicate the presence of systematic differences between elite athletes and nonathletes on motor abilities related to experience in this sport.